Folkloric Language of the Dream: Oneiric Narratives in the Social Communication - Ivanauskaitė-Šeibutienė, Vita (Tautosakos darbai, 2014)
In culture research, just like in psychology, there is a tendency of defining dreams as specific language, characterized by its unique structure and meaning. Thus, distinction between absolutely individual language of the dream, which is, according to the cultural scholar Yuri Lotman, unsuited to communication, and the language of the dream narrative, which turns private oneiric experience into a public social performance, directly connected to tradition and social communication, acquires particular relevance.Here, several relevant aspects of the dream narratives as elements of the traditional communication are examined in greater detail. While studying the dream narratives recorded in the course of approximately a decade in various parts of Lithuania, it was noted that narrators belonging to the elder generation quite frequently refer to delivering a message gained in the dream (i. e., when the dreamer believes to have dreamt of something significant) to a person that has been dreamt of or is closely related to the deceased appearing in the dream (in order to warn or inform the person in question of something, or in order to encourage them to take certain action). The article is focused on the ways that such communication of the dream message affects the behavior of the community members and their relationships. Another group of the dream narratives analyzed in the article consists of stories about the deceased applying for help in the dreams. Here, narratives involving the deceased unexpectedly turning up in the dreams of strangers (not the family members or relatives) and asking for something, are considered. Like the whole paradigm of oneiric narratives associated with the requests of the deceased in general, these narratives support the essential notion shaped by tradition and religious practices: namely, that requests from the deceased are never accidental (the deceased only apply for help when it is necessary) and must be granted immediately. It seems that in such atmosphere of full-scale caring about the deceased sighted in dreams, the opposition of one’s own vs. strange is totally abolished.The dream narratives as elements of traditional communication correspond to the general view supported by many researchers maintaining that folklore is a communication phenomenon par excellence, provided it is viewed not just as a jumble of separate pieces, but rather as a continuous flow of tradition, as ways and processes of supporting the communal ties and mutual understanding, of sharing values and living accordingly.
Keywords: -